Chorus : a novel - Kauffman, Rebecca (Counterpoint, 2022)
"The seven Shaw siblings have long been haunted by two early and profoundly consequential events. Told in turn back and forth over time, from the early twentieth century through the 1950s, each sibling relays their own version of the memories that surround both their mother's mysterious death and the circumstances leading up to and beyond one sister's scandalous teenage pregnancy. As they move into adulthood, the siblings assume various new roles: caretaker to their aging father, addict, enabler, academic, decorated veteran, widow, and mothers and fathers to the next generation. A family knot of entanglement, each sibling encounters divorce, drama, and death, while haunted by a mother who was never truly there. Through this lens, they all seek to not only understand how her death shaped their family, but also to illuminate the insoluble nature of the many familial experiences we all encounter-the concept of home, the tenacity that is a family's love, and the unexpected ways through which healing can occur. Chorus is a hopeful story of family, of loss and recovery, of complicated relationships forged between brothers and sisters as they move through life together, and the unlikely forces that first drive them away and then ultimately back home"--